32. Phrenic nerve study in infants: Normative data and technical aspects in Verona experience. Issue 4 (April 2016) - Romito, S.; Segatti, A.; Alessandrini, L.; Donato, F.; Squintani, G.; Moretto, G.
Abstract : The evaluation of phrenic nerve conduction is an important technique for assessing ventilatory function. Slightly different methods are described in literature for adults and children, and studies with normative data in infants are few. We present our study aimed at collecting normative data of phrenic nerve conduction in infants. Diaphragmatic action potentials (DAPs) were bilaterally recorded from 16 neurologically healthy babies aged 0–6 months. The active electrode was placed over the xiphoid process and the reference electrode over the chest margin, on the mid-clavicular line or 1 cm laterally, ipsilaterally to the stimulation side. Transcutaneous electrical stimulation of 0.1 ms duration was applied over the phrenic nerve between the clavicular and the sternal heads of sternocleidomastoideus (SCM) muscle. Peak-to-peak DAP amplitude, onset latency, DAP area and interside differences were analysed. M-wave amplitude mean value was 2.3 mV (DS 0.8 mV) and its latency mean value was 5.4 ms (DS 0.7 ms). Our technique is slightly different from those of previous reports in children and let us to obtain always clearly reproducible DAPs, with higher amplitudes than in other works. Moreover this method allows a precise pre-/post-operative comparison in children undergoing surgery with a great risk of phrenic nerve damage.